2012
DOI: 10.1080/14616734.2012.744733
|View full text |Cite
|
Sign up to set email alerts
|

Children's attachment-related self-worth: a multi-method investigation of postdivorce preschoolers’ relationships with their mothers and peers

Abstract: Three related hypotheses derived from attachment theory were examined in this multi-informant and multi-method study of 71 postdivorce mothers and their preschool children (40 boys, 31 girls): (1) mother-child interactions observed at home will be related to attachment-related representations by children (Attachment Story Completion Task or ASCT) and mothers (Parent Attachment Interview or PAI); and (2) these variables will be inversely correlated with maternal depressive symptoms and positively with social su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 49 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, in the present investigation there was no control for parental psychopathology, nor was there information on the quality of the parents' relationship to one another. Considering recent evidence that maternal depression and marital conflict may impact on children's self‐worth (Bretherton, Gullon‐Rivera, Page, Oettel, Corey & Golby, ), future investigations should incorporate these variables. Also, despite the accurate self‐description a child can provide with the PSPCSA, the method does not include a measure of truthfulness.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the present investigation there was no control for parental psychopathology, nor was there information on the quality of the parents' relationship to one another. Considering recent evidence that maternal depression and marital conflict may impact on children's self‐worth (Bretherton, Gullon‐Rivera, Page, Oettel, Corey & Golby, ), future investigations should incorporate these variables. Also, despite the accurate self‐description a child can provide with the PSPCSA, the method does not include a measure of truthfulness.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of single parenting, mothers take on a particularly critical role in supporting the development of a healthy and functional family environment (Bretherton et al . ). Thus, identifying and reducing depressive symptoms among mothers who have histories of IPV may be a key pathway to promoting longer‐term family health and well‐being.…”
Section: Discussionmentioning
confidence: 97%
“…Close and supportive mother–child relationships are important to children's postdivorce adjustment (Bretherton et al . ). Divorced families are less hierarchical and more egalitarian than are two‐parent families (Perrin et al .…”
Section: Background: Theoretical Framework and Literature Reviewmentioning
confidence: 97%
“…Narrative assessments with traumatized children exposed to maltreatment have shown that they represent significantly more frightening and violent imagery, and that the structures of their narratives are more likely to be incoherent, suggesting emotional and behavioral dysregulation and incomplete processing of frightening memories (Heller et al, 2006; Hodges et al, 2000; MacFie et al, 2001). Narrative assessments have also been shown to correspond with interactional qualities observed in the home (Bretherton et al, 2013; Dubois-Comtois and Moss, 2008; Goodman et al, 1998), and actual behavior changes parents made in response to their participation in a parenting intervention (Toth et al, 2002).…”
Section: Narrative Story-stem Techniquesmentioning
confidence: 92%